Antibiotic Use in Cesarean Section and Hysterectomy Procedure: Qualitative and Quantitative Assessment - Mahendra, Andika Dwi (Indonesian Journal of Pharmaceutical and Clinical Research, 2021)
Antibiotic resistance is global issue and the incident is increasing with the use of unwise antibiotic. This study is to describe and evaluate appropriateness of antibiotic prophylaxis selection on Cesarean Section and Hysterectomy procedure. Purpose of study is to evaluate appropiateness of antibiotic selection on cesarean section and hysterectomy. A retrospective study was performed during September 2016 - January 2017 in Private Hospital, Semarang. Data were analized quantitatively using ATC-DDD methodology. Evaluation of antibiotic prophylaxis will be assessed based on The guideline of The American College of Obstetricians and Gynecologists (ACOG) : Antibiotic Prophylaxis for Gynecologic Procedures and The American Society of Health-System Pharmacists (ASHP) : Clinical Practice Guidelines for Antimicrobial Prophylaxis in Surgery. Overall, 90 of 95 patients were given antibiotic prophylaxis. The most frequently used antibiotics were ceftriaxone (69.51 DDD/Patient-days) and ceftazidime (14.95 DDD/Patient-days). Appropriate antibiotic selection based on the guidelines for cesarean section procedure was 1.75% and 6.1% for hysterectomy procedure. The use of antibiotic prophylaxis on cesarean section and hysterectomy procedure was very high and less appropriate in the selection. Almost patient received third-generation cephalosporin instead of first-generation cephalosporin such as cefazolin. cefazolin is more effective and narrow spectrum for infection-causing bacteria of these procedures.